HOW TO DEAL WITH BURNOUT DURING ONLINE LEARNING IN MEDICAL EDUCATION? A SYSTEMATIC REVIEW - Arigi, Lalu Ahmad Gamal; Mustika, Rita; Greviana, Nadia (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background: During their education, medical students face various types of stress in medical school. The COVID-19 pandemic has caused significant changes in communication. Technology improves the usage of telecommunications in medical education, making students spend more time staring at screens, tablets, and smartphones, which may affect stress and lead to burnout. This study aims to explore burnout and strategies for reducing the occurrence of burnout in students during online learning.Method: This study is a systematic review aimed at exploring the burnout phenomena in medical students doing online learning and strategies to prevent it. The journal articles were sought from the PubMed, Google Scholar, and Springerlink databases. We applied the inclusion and exclusion criteria to select the relevant journal articles. We analyze the validity and review the articles descriptively. Results: After the systematic selection of the journal articles, there are 28 full journals related to burnout and prevention strategies. The result defines Burnout as an individual's reaction to long-term work stress that lasts for a long time and can become chronic. In this article, six strategies can be used by institutions, educators, and students to help overcome the incidence of burnout during online learning.Conclusion: There is a need for a strategy carried out by institutions that provide facilities to provide emotional support to students; develop educators to prevent burnout during the learning process; apply healthy practices in preventing the eyes from doing ice-breaking between online learning sessions, and use various visual interactive learning methods to increase the interest and motivation of students to avoid burnout during online learning.